Anti-signal recognition particle antibody in patients without inflammatory myopathy: a survey of 6180 patients with connective tissue diseases. (2nd January 2016) - Hanaoka, H; Kaneko, Y; Suzuki, S; Takada, T; Hirakata, M; Takeuchi, T; Kuwana, M
Abstract : Objectives : To clarify the prevalence of anti-signal recognition particle (anti-SRP) antibody in connective tissue diseases (CTDs) and investigate the clinical characteristics of patients without inflammatory myopathy. Method : Sera from 6180 patients with CTD were examined by immunoprecipitation (IPP) assays, and the records of patients positive for anti-SRP antibody were reviewed retrospectively. The antibody against the 54-kDa protein of SRP (SRP54) was quantified by enzyme-linked immunosorbent assay (ELISA) in patients with anti-SRP antibody. Results : Of the 28 patients positive for anti-SRP antibody, nine (32.1%) did not have inflammatory myopathy. The clinical diagnoses and characteristics of those patients varied considerably. In patients with inflammatory myopathy, the index of anti-SRP54 was much higher than in those without myopathy (1.15 vs. 0.46; p = 0.036). Conclusions : The prevalence of anti-SRP antibody was 0.5% in a cohort of Japanese patients with CTD, and one-third of them did not have inflammatory myopathy. Sera from patients with inflammatory myopathy recognized SRP54 more strongly than in those without myopathy.